2004
DOI: 10.1016/j.neuron.2004.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Range Attraction of Cortical GABAergic Interneurons by Neuregulin-1

Abstract: Most cortical interneurons arise from the subcortical telencephalon, but the molecules that control their migration remain largely unidentified. Here, we show that different isoforms of Neuregulin-1 are expressed in the developing cortex and in the route that migrating interneurons follow toward the cortex, whereas a population of the migrating interneurons express ErbB4, a receptor for Neuregulin-1. The different isoforms of Neuregulin-1 act as short- and long-range attractants for migrating interneurons, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
443
5
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(472 citation statements)
references
References 57 publications
23
443
5
1
Order By: Relevance
“…A function for Nrg1 on directing the migration of ErbB4-expressing, MGE-derived INs has been previously reported by Flames et al [23], but our findings fundamentally differ from theirs. Whereas we demonstrate that Nrg1 isoforms and Nrg3 act through ErbB4 to inhibit or repel migrating MGE-derived INs, Flames et al [23] concluded that the membrane-attached isoform of Nrg1 (Nrg1-type III; referred to as Nrg1-CRD by Flames et al [23]) provides a growth permissive corridor through the developing striatum and that the secreted Ig isoform of Nrg1 (Nrg1-type I; referred to as Nrg1-Ig by Flames et al [23]) attracts INs from the vTel into the cortex and along the IZ.…”
Section: Discussioncontrasting
confidence: 57%
“…A function for Nrg1 on directing the migration of ErbB4-expressing, MGE-derived INs has been previously reported by Flames et al [23], but our findings fundamentally differ from theirs. Whereas we demonstrate that Nrg1 isoforms and Nrg3 act through ErbB4 to inhibit or repel migrating MGE-derived INs, Flames et al [23] concluded that the membrane-attached isoform of Nrg1 (Nrg1-type III; referred to as Nrg1-CRD by Flames et al [23]) provides a growth permissive corridor through the developing striatum and that the secreted Ig isoform of Nrg1 (Nrg1-type I; referred to as Nrg1-Ig by Flames et al [23]) attracts INs from the vTel into the cortex and along the IZ.…”
Section: Discussioncontrasting
confidence: 57%
“…Results clearly show that wt ST14A cells have a low basal intrinsic motility that is not altered by the presence of NMDA (Figure 1C). On the other hand, NMDA could have no effect per se in ST14A cell migration, and have instead an effect when added together with other molecules, such as members of the neuregulin family, and specifically NRG1, that has been shown to promote ErbB4 mediated neuronal migration [6-8]. Wt ST14A cells do not express ErbB4; however, they express other ErbB receptors, which could mediate a NRG1-induced response in the presence of NMDA.…”
Section: Resultsmentioning
confidence: 99%
“…Receptor-ligand interaction induces the homo- or heterodimerization with other members of the ErbB receptor family, which in turn results in the activation of several intracellular signalling pathways and the induction of cellular responses including migration of neuronal precursor cells [4-6]. In vivo studies demonstrate that the NRG1/ErbB4 system is involved in tangential migration of olfactory bulb (OB) interneuron precursors in the rostral migratory stream (RMS) [7] and of cortical interneuron precursors migrating from the ventral telencephalon [8]. …”
Section: Introductionmentioning
confidence: 99%
“…66 Furthermore, different isoforms of NRG1 appear to act as attractants for migrating cortical GABAergic interneurons. 108 These findings are highly intriguing given the reported association between the NRG1 gene and schizophrenia, 33,[52][53][54][55][56][57][58][59] and suggest that defects in GABA A receptor regulation by NRG1 is a possible mechanism by which NRG1 contributes to schizophrenia. Indeed, in a previous study using the same 33 discordant sibpairs as in the present study, we found higher expression of the SMDF isoform of NRG1 in subjects with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%